2021
DOI: 10.1101/2021.07.16.451448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deforestation projections imply range-wide population decline for critically endangered Bornean orangutan

Abstract: Assessing where wildlife populations are at risk from future habitat loss is particularly important for land-use planning and avoiding biodiversity declines. Combining projections of future deforestation with species density information provides an improved way to anticipate such declines. Using the endemic and critically endangered Bornean orangutan (Pongo pygmaeus) as a case study we applied a spatio-temporally explicit deforestation model to forest loss data from 2001-2017 and projected future impacts on or… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Several investigations have identified that the male range is significantly greater compared to females due to the food availability. Despite the increase in deforestation, the orangutan population has shown the opposite trend (Santika et al 2017a;Maria Voigt et al 2021Wich et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have identified that the male range is significantly greater compared to females due to the food availability. Despite the increase in deforestation, the orangutan population has shown the opposite trend (Santika et al 2017a;Maria Voigt et al 2021Wich et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The estimate of collection density in Borneo is much less than Java at a ratio of 35:199 collections per 100 km 2 (Middleton et al 2019). As a biodiversity hotspot, Borneo urgently needs effective conservation actions (Voigt et al 2021). Basic biodiversity research that includes botanical explorations is one crucial activity that will help accelerate the planning and formulation of conservation plans in Borneo (Hairah et al 2017;Sabran et al 2014).…”
Section: Introductionmentioning
confidence: 99%